Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian Rumah pada PT Harmony Land Group di Kota Depok - Annisa Agistya; Isnurrini Hidayat Susilowati (STIKes Ibnu Sina Ajibarang, 2025)
Competition in the property industry requires development companies to implement the right marketing strategy to attract consumer interest. Effective promotion and strategic location selection are important factors in influencing home buying decisions. This study aims to determine how much influence promotion and location have, both partially and simultaneously, on house purchase decisions at PT Harmony Land Group in Depok City. The research method used is a quantitative approach with purposive sampling technique on 63 respondents. Data collection was carried out through questionnaires, observations, and literature studies, and analyzed using SPSS version 25 through validity, reliability, classical assumption, multiple linear regression, t test, and F test tests. The results showed that promotion has a significant effect on purchasing decisions (sig. 0.000 < 0.05; t count 6.231 > t table 2.00030), as well as location (sig. 0.028 < 0.05; t count 2.252 > t table 2.00030). Simultaneously, promotion and location have a significant effect on purchasing decisions with a calculated F value of 25.949> F table 2.39 and a significance of 0.000 <0.05. This finding confirms that optimal promotion and strategic location can increase house purchase decisions.